2019
DOI: 10.1002/ajb2.1215
|View full text |Cite
|
Sign up to set email alerts
|

Allometry of the pyrophyticAristidain fire‐maintained longleaf pine–wiregrass ecosystems

Abstract: Premise of the Study Aboveground biomass (AGB) of herbaceous vegetation is a primary source of fuel in frequent surface fires that maintain grasslands, savannas, and woodlands. Methods for nondestructively estimating AGB are required to understand the mechanisms by which fuels affect fire behavior and the effects of time since the last burn. We developed allometric equations to estimate AGB in wiregrass (Aristida beyrichiana/A. stricta), a dominant bunchgrass in Pinus palustris ecosystems and a key species for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…The primary grass species at Pebble Hill is wiregrass (Aristida stricta), as opposed to a broader mix of grasses at Eglin. Shearman et al (2019) reported that basal volume of the grass tussock was a strong predictor of total aboveground biomass of wiregrass clumps, also describing a local range of biomass at fine scales (both live and dead) at approximately ±200 g. From our results, we hypothesize that biomass density is more variable than suggested by occupied volume estimates.…”
Section: Estimates Of Fuel Mass From Occupied Volumesupporting
confidence: 57%
“…The primary grass species at Pebble Hill is wiregrass (Aristida stricta), as opposed to a broader mix of grasses at Eglin. Shearman et al (2019) reported that basal volume of the grass tussock was a strong predictor of total aboveground biomass of wiregrass clumps, also describing a local range of biomass at fine scales (both live and dead) at approximately ±200 g. From our results, we hypothesize that biomass density is more variable than suggested by occupied volume estimates.…”
Section: Estimates Of Fuel Mass From Occupied Volumesupporting
confidence: 57%
“…, Crone and Rapp ). Increased fire‐free periods have been shown to have a negative effect on live aboveground biomass for a given sized wiregrass tussock (Shearman et al., ). Presumably, long fire‐free periods would also reduce belowground biomass such as nonstructural carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…Resource budget models are hypothesized to be a mechanism for synchronized masting in plants and assume that individual plants will only flower when they reach a certain threshold of stored nonstructural carbohydrate reserves (Crone et al 2009, Crone andRapp 2014). Increased fire-free periods have been shown to have a negative effect on live aboveground biomass for a given sized wiregrass tussock (Shearman et al, 2019). Presumably, long fire-free periods would also reduce belowground biomass such as nonstructural carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…Wiregrass, the dominant herbaceous component in this ecosystem, has a dense crown closer to the forest floor and accumulates senesced material around the crown [40][41][42]. Given that these plots had two years of growth since the last fire and a long history of frequent fire (40 years) [39], our results corroborated that the crown was dense enough to have a different bulk density than the upper portions of the plant [42]. As such, applying a height metric for herbaceous fuel estimates is required to accurately represent the vertical distribution of a major component of the fuelbed.…”
Section: Discussionmentioning
confidence: 99%